The Implementation of Street Vendors Regulation Policy in Developing their Social Order in Majalaya Area of Bandung Regency - Desti, Indria (Universitas Pendidikan Indonesia, 2020)
This study was motivated by the problems caused by the presence of Pedagang Kaki Lima (PKL) or street vendors in public space. Their selling activity on the sidewalks and pavements around Majalaya area was considered less organized and as an inconvenience to social orderliness such as the traffic. This study aims to describe the implementation of street vendors regulation policy in developing their social order in Majalaya Area of Bandung Regency. This study applied a qualitative approach with descriptive method. The data was collected through observation, interview, and documentation study. This study found that: 1) before the regulation was implemented, there were many street vendors booths which were illegal, and the condition was actually less ordered and inappropriate thus it impaired the convenience to streetwalkers and road traffic; 2) the deliberate action by Satpol PP or the civil service police unit concerning the regulation of street vendors are to organize, foster, and discipline them according to the Local Regulation Number 5/2015 with persuasive approach to give a good comprehension and motivation. Moreover, the study also discovered that the country authority allowed them to have selling activities and build a temporary booth near the Majalaya bus station and shop grounds, and dismantled the illegal booths which besides disturbing the public orderliness but also the public concerns loyalty; and 3) the implementation of the regulation was still unmaximized since there were no feasible locations to accommodate all the street vendors, the crowds and accessibility of Alun-alun or the city square caused the street vendors tend to ignore the rules, and there was some economic factors caused street vendors find the sustenance to meet their daily needs.